Handbook of theory and practice of sustainable development in higher education - Leal Filho, Walter (2019)
This Handbook approaches sustainable development in higher education from an integrated perspective, addressing the dearth of publications on the subject. It offers a unique overview of what universities around the world are doing to implement sustainable development (i.e. via curriculum innovation, research, activities, or practical projects) and how their efforts relate to education for sustainable development at the university level. The Handbook gathers a wealth of information, ideas, best practices and lessons learned in the context of executing concrete projects, and assesses methodological approaches to integrating the topic of sustainable development in university curricula. Lastly, it documents and disseminates the veritable treasure trove of practical experience currently available on sustainability in higher education.